1995
DOI: 10.1172/jci117836
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin stimulates Cl- transport in ascending thin limb of Henle's loop in hamster.

Abstract: IntroductionThe effect of arginine vasopressin (AVP) on Invest. 1995Invest. . 95:1623Invest. -1627

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The regulation of both CFTR and ClC-2 expression by AVP, the main hormone involved in the regulation of body fluid osmolality, suggests that these two proteins may be involved in the kidney's ability to concentrate and dilute the urine. This hypothesis is supported by results obtained by other authors, showing that AVP increases Cl -reabsorption in thick ascending limb of Henle's loop and cortical collecting duct cells [8,9,10,23,34,36].…”
Section: Discussionsupporting
confidence: 87%
“…The regulation of both CFTR and ClC-2 expression by AVP, the main hormone involved in the regulation of body fluid osmolality, suggests that these two proteins may be involved in the kidney's ability to concentrate and dilute the urine. This hypothesis is supported by results obtained by other authors, showing that AVP increases Cl -reabsorption in thick ascending limb of Henle's loop and cortical collecting duct cells [8,9,10,23,34,36].…”
Section: Discussionsupporting
confidence: 87%
“…One such piece of evidence is the functional regulation of chloride transport in the tAL by vasopressin. Takahashi et al [17]reported an increase in chloride permeability in the tAL induced by vasopressin treatment. They concluded that this effect was mediated by the signal through the V2 receptor, suggesting that, when vasopressin secretion is increased, i.e., under a condition where the body needs a higher urine concentration, the chloride transport in the tAL should also increase, probably through CLC-K1.…”
Section: Indirect Evidence That Clc-k1 May Be Important For Urinary Cmentioning
confidence: 99%
“…Previously, we have demonstrated 3 independent factors: pH, Ca 2+, and vasopressin, that affect C1-transport. 24,25,42,55,56 In 1987, we first described how the ambient acidification of the ascending thin limb suppresses the C1-transport in hamster ascending thin limb. 24 Both luminal and basolateral acidification remarkably inhibited C1-transport.…”
Section: Regulation Of Chlorine Ion Transportmentioning
confidence: 99%
“…42 The effect of arginine vasopressin on CI-transport was investigated by measuring t r a n s e p i t h e l i a l voltage and t r a n s m u r a l 22Na-36C1 flux. In the presence ofa transmural NaC1 concentration gradient (100 mmol/L higher in the lumen), transepithelial voltage was 8.4 mV.…”
Section: Regulation Of Chlorine Ion Transportmentioning
confidence: 99%